The mediating effect of knowledge sharing between intrinsic motivation, high-performance work system, authentic leadership on employees' creativity in Pakistan territory education institutions - Ul Hassan, Syed Ibn (2021)
In recent management literature, employee creativity is considered to be an essential factor in achieving positive work outcomes and organizational effectiveness”. Most prior studies have explored the role of psychosocial factors in explaining employee creativity. However, in this stream of research, the role of individual and organizational factors in enhancing employee creativity has gained little attention. This specific research intended to analyse the relationship between the authentic leadership, high-performance work systems and intrinsic motivation on the creativity of the employees. In addition, this particular research also analysed the mediating impact of knowledge sharing between authentic leadership, high-performance work systems and intrinsic motivation on the creativity of the employees. Two crucial theories have been investigated in this study namely self-determination theory as well as social exchange theory. In order to constitute the sample of the research, the researcher selected random sampling technique and selected 313 faculty members who were the full-time faculty members at the Public Universities of Punjab, Pakistan. The researcher integrated a self-administrated questionnaire in order to accomplish the aim and objectives of the study. The data collected through this research design was analysed by the means of PLS-SEM approach using Smart PLS 3.2.8. The outcomes of the research indicated that there is a position association between all the variables of the research and the creativity of the employees in the organization. The outcomes of the research also pointed out that there is a positive association among high performing work system, intrinsic motivation, and knowledge sharing. The knowledge sharing act as a partial mediator for the relationship between employee creativity, high-performing working systems and at the same time authentic leadership. The outcomes of this research are valuable for the policy-making as well as regulators and it could facilitate them in escalating the level of high-performance work system, authentic leadership and at the same time intrinsic motivation.